Balancing Intermolecular Interactions between Acceptors and Donor/Acceptor for Efficient Organic Photovoltaics. (4th September 2021) - Han, Chenyu; Wang, Jianxiao; Chen, Liangliang; Chen, Jingfei; Zhou, Long; Wang, Pengchao; Shen, Wenfei; Zheng, Nan; Wen, Shuguang; Li, Yonghai; Bao, Xichang
Abstract: Promoted by uninterrupted materials and device innovation, organic solar cells have achieved impressive development. However, the complicated intermolecular interactions inside active layers are less understood. Herein, the intermolecular interactions are studied from the dual perspectives of acceptor/acceptor (A/A) and donor/acceptor (D/A), and how these interactions synergistically control the final efficiencies. Three small molecular acceptors (SMAs) are designed with different end‐caps, which manipulate the crystallinity and electrostatic potential (ESP) distributions of acceptors, and accordingly, the A/A and D/A intermolecular interactions. The results show that SMA LA17 with low A/A interactions exhibits inferior performance around 12%, owing to its strong D/A interaction with donor PM6, which shapes too miscible morphology and increases charge recombination. Instead, LA16 with strong A/A interactions and moderate D/A interactions delivers improved bulk‐heterojunction (BHJ) networks, and therefore, enhances charge transport and diminishes geminate or trap‐assisted charge recombination. Consequently, PM6:LA16 records the competitive efficiency of up to 13.74% among the three systems. Therefore, this study deepens the synergistic or balancing effect of the D/A and A/A interactions on BHJ blends for efficient organic solar cells. Abstract : The complicated intermolecular interactions in bulk‐heterojunction (BHJ) play a fundamental role in organic photovoltaics. This study implies that the interactions between acceptors (A/A) and donor/acceptor (D/A) interactions synergistically control the nanoscale networks of BHJ and exciton/charge behaviors. Therefore, balancing these two kinds of intermolecular interactions should be well considered for constructing high performance organic photovoltaics.